Peran Perilaku Kelompok dalam Meningkatkan Kualitas Hubungan Interpersonal di MAN 1 Tanah Datar - Emelia, Rita; Despatriani, Despatriani; Asmendri , Asmendri; Sari, Milya (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study explores the role of group behavior in improving the quality of interpersonal relationships in MAN 1 Tanah Datar, focusing on the context of learning English lessons during the pandemic. This study used a qualitative approach with a descriptive method. The research methods used include data collection through observation, interviews, and documentation studies, followed by comprehensive data analysis using the VosViewer method to analyze the relationship of publications with historical and institutional; author and institutional relations; and dissemination of PAI knowledge. The results showed that the transition to online learning during the pandemic has affected the effectiveness of teachers' observations of children's character and moral values in English lessons. Leadership in the context of Islamic education is also an important factor in directing group behavior towards efforts to improve the quality of interpersonal relationships. Group dynamics and character education also contribute significantly in strengthening the quality of interpersonal relationships in MAN 1 Tanah Datar. With these findings in mind, the study provides valuable insights for the development of educational strategies that are more effective in improving the quality of interpersonal relationships in English learning environments.